A sodium supplement additive and its use in sodium ion batteries

By using PVDF grafts as sodium supplementation additives in sodium ion battery positive electrode sheets, the first Coulomb efficiency and cycle life of hard carbon negative electrode materials is solved, the energy density and cycle life of the battery are improved, and the battery cell preparation is reduced Difficulty, achieving efficient performance improvement of sodium ion battery.

CN118763177BActive Publication Date: 2025-01-10ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411241079.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-10
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Hard carbon, as the negative electrode material for sodium ion batteries, has low efficiency, resulting in serious loss of active sodium, reduced battery energy density and cycle life, and the existing pre-sodiumization methods have safety hazards and operation difficulties, and are inefficient.

Method used

Using PVDF graft as sodium supplement additive, a high sodium content of sodium-ion battery cathode sheet is prepared by mixing it with the positive electrode main material, conductive agent and adhesive, which improves the first Coulomb efficiency and cycle life of the sodium-ion battery and reduces the Difficulty in preparing battery cells.

Benefits of technology

It significantly improves the first Coulomb efficiency and energy density of sodium ion batteries, extends the cycle life of the battery, reduces the difficulty of cell preparation, and provides excellent rate performance and cycle durability at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118763177B_ABST
    Figure CN118763177B_ABST
Patent Text Reader

Abstract

The present invention discloses a sodium supplement additive and its use in a sodium ion battery, belonging to the technical field of sodium ion batteries. The present invention discloses a sodium ion battery positive electrode sheet, comprising: a base layer, and a functional layer attached to the base layer, wherein the functional layer has an adhesive, and the adhesive comprises at least one of PTFE, PVDF, and a PVDF graft, wherein the PVDF graft has a hydroxypropyl methacrylate group and / or a methacrylate 2-ethanesulfonate group. The present invention also discloses a method for preparing a sodium ion battery positive electrode sheet. The sodium ion battery positive electrode sheet of the present invention can effectively improve the first coulomb efficiency and energy density of the sodium ion battery, and can also improve the cycle life of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and particularly relates to a sodium supplement additive and application thereof in sodium ion batteries. Background Art

[0002] Sodium-ion batteries have attracted widespread attention in recent years due to their advantages such as abundant raw materials, excellent low-temperature performance, and high safety. Hard carbon is currently considered one of the most promising negative electrode materials for sodium-ion batteries. However, factors such as the large specific surface area and more surface active sites of hard carbon result in low initial coulombic efficiency, severe loss of active sodium, and reduced battery energy density and cycle life.

[0003] At present, it is believed that the more effective solution is pre-sodiumization. The main means of existing pre-sodiumization are: 1. physical sodium sheet contact; 2. electrochemical pre-sodiumization; 3. short-circuit pre-sodiumization, etc. The main problems with these methods are: metallic sodium has safety hazards during use, and metallic sodium is easily oxidized, which leads to difficult process operation, low efficiency, and difficulty in integrating into the existing battery preparation process.

[0004] The invention application with publication number WO2023097984A1 relates to a positive electrode material and a preparation method thereof, a positive electrode sheet, and a sodium ion battery. The application discloses a method of adding a sodium supplement during the preparation of the positive electrode material. The sodium supplement used includes sodium sulfide, a conductive agent, and a catalyst, which can effectively compensate for the sodium loss at the negative electrode during the first charge and improve the initial coulomb efficiency. However, the stability of the sodium supplement in this scheme cannot be effectively guaranteed, and the effect of improving the initial coulomb efficiency still needs to be further improved, and the cycle life of the sodium ion battery has not been effectively improved. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium supplement additive with high sodium content and stable performance and its use in sodium ion batteries, which can not only effectively improve the first coulombic efficiency and energy density of sodium ion batteries, but also improve the cycle life of sodium ion batteries.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A sodium ion battery positive electrode sheet, comprising a substrate sheet and a functional layer attached to the substrate layer, wherein the functional layer comprises a positive electrode slurry; the positive electrode slurry comprises a positive electrode main material, an adhesive, a conductive agent and a sodium supplement additive; by weight, the positive electrode main material is used in an amount of 90-98 parts, the adhesive is used in an amount of 1-5 parts, and the conductive agent is used in an amount of 1-5 parts; the sodium supplement additive is used in an amount of 0.1-1.0wt% of the positive electrode main material;

[0008] The adhesive includes at least one of PTFE, PVDF, and PVDF grafts.

[0009] Preferably, the sodium supplement additive is at least one of sodium carbonate, sodium oxalate, sodium gluconate, sodium acetate, etc.

[0010] Preferably, the positive electrode main material includes at least one of layered oxides, Prussian blue and its analogs, and polyanionic compounds.

[0011] Preferably, the conductive agent includes at least one of a carbon material, a metal oxide, and a conductive polymer.

[0012] According to one embodiment of the present invention, the PVDF graft is prepared by reacting hydroxypropyl methacrylate, sodium salt of 2-ethanesulfonate methacrylate and PVDF.

[0013] PVDF is modified by using hydroxypropyl methacrylate and sodium salt of 2-ethanesulfonate methacrylate, and hydroxypropyl methacrylate groups and / or 2-ethanesulfonate methacrylate groups are introduced into PVDF to obtain a PVDF grafted product.

[0014] The use of PVDF grafts as adhesives has excellent bonding strength and high mechanical strength. Compared with PVDF, PVDF grafts introduce related groups of hydroxypropyl methacrylate and / or 2-ethanesulfonic methacrylate, which makes it have a more complex spatial structure. In the process of preparing sodium ion positive electrode sheets, the structural uniformity of the positive electrode slurry is improved, and the diffusion of sodium ions at the interface of the electrode and the electrolyte can be enhanced in the subsequent charge and discharge. In addition, the introduced groups contain oxygen and / or sulfur elements, which are beneficial to the insertion and extraction of sodium ions, improve the electronic and ionic conductivity, and help optimize the electrochemical performance of the battery.

[0015] Preferably, 4 mL to 6 mL of hydroxypropyl methacrylate and 0.2 g to 0.5 g of sodium methacrylate 2-ethanesulfonate are used for every 10 g of PVDF.

[0016] According to one aspect of the present invention, a method for preparing a PVDF grafted product is provided, wherein hydroxypropyl methacrylate and sodium salt of 2-ethanesulfonate methacrylate are reacted with PVDF as a substrate under the protection of nitrogen by ATRP method. DMF is used as a solvent and CuCl is used as a catalyst during the reaction. Specifically, the following steps are included:

[0017] First, add PVDF powder into DMF at a ratio of 70 mL to 90 mL DMF for every 10 g PVDF, and heat and stir at 45°C to 60°C until the powder is completely dissolved.

[0018] Then, hydroxypropyl methacrylate and DMF were weighed in proportion, stirred and dissolved, and then sodium methacrylate 2-ethanesulfonate was added, and the sodium methacrylate 2-ethanesulfonate and hydroxypropyl methacrylate were fully mixed by stirring. Then, the DMF solution of the dissolved PVDF powder was added.

[0019] Under the protection of nitrogen, ATRP reaction was carried out. In the above solution, appropriate amount of CuCl and DMF were added according to the ratio of 60mgCuCl and 5mL DMF for every 10g PVDF, and the reaction temperature was controlled at 85℃-95℃ and the reaction time was 5h-8h. After the reaction was completed, after the mixture was cooled to room temperature, an excess of petroleum ether-ethanol with a volume ratio of 1:1 was added for precipitation, and the precipitate was obtained by centrifugation, and the precipitate was repeatedly washed with a large amount of ethanol-water with a volume ratio of 1:1. Finally, the obtained precipitate was dried to obtain a PVDF grafted product.

[0020] The invention also discloses the application of the sodium supplement additive in preparing a positive electrode sheet of a sodium ion battery.

[0021] The method for preparing a positive electrode sheet of a sodium ion battery using the above-mentioned sodium supplement additive mainly comprises the following steps:

[0022] S1. Mix the sodium supplement additive with the positive electrode material and the adhesive until the solid is completely dissolved;

[0023] S2. Adding a conductive agent to the material obtained in step S1 to prepare a positive electrode slurry;

[0024] S3. The positive electrode slurry obtained in step S2 is coated on the base layer to form a positive electrode sheet.

[0025] Preferably, in step S1, the positive electrode main material and the sodium supplement additive are added to a stirring tank for mixing; the speed of the stirring tank is controlled to be 10RPM-30RPM, and the time is 4h-12h.

[0026] Preferably, in step S2, the conductive agent is added to the stirring tank where the material in step S1 is located, and the speed of the stirring tank is controlled to be 10RPM-30RPM, and the kneading time is 1h-3h.

[0027] Preferably, the base layer comprises a metal-based material or an alloy-based material, and the metal-based material comprises an aluminum-based material or a copper-based material.

[0028] According to one aspect of the present invention, in the process of preparing the positive electrode of the sodium ion battery, when the PVDF graft is used as the adhesive, furfuryl thiopropionate can be added in step S1 or step S2, wherein the mass ratio of furfuryl thiopropionate to the PVDF graft is 1:3-5.

[0029] The addition of furfuryl thiopropionate can optimize the improvement of the electrochemical performance of PVDF grafts for the first coulombic efficiency sodium-ion battery. This may be due to the presence of heterocyclic rings and carboxylate groups in furfuryl thiopropionate. Due to the complexity of its spatial structure, it is possible to form a coordinated structure with the PVDF graft. The presence of sulfur elements, oxygen elements, etc. will cause changes in the spatial structure of the PVDF graft due to their electronegativity differences, which is more conducive to the insertion and extraction of sodium ions and promotes the diffusion of sodium ions in the electrolyte, thereby compensating for the slow diffusion of sodium ions due to their larger radius than lithium ions.

[0030] According to one aspect of the present invention, the above-mentioned positive electrode sheet and the hard carbon negative electrode sheet can be assembled into a sodium ion battery.

[0031] Preferably, a hard carbon negative electrode sheet and a PP diaphragm or a PE diaphragm are used to cooperate with the above-obtained positive electrode sheet, and a dry battery cell is assembled in a stacking manner, and then encapsulated with an aluminum plastic film, an electrolyte is injected, and then formation is waited. The formation upper limit voltage is controlled to 4.0V-4.5V to obtain a sodium ion battery. Under high voltage, the sodium supplement additive can decompose to produce active sodium to make up for the sodium consumed by the negative electrode hard carbon.

[0032] The present invention also discloses the application of the sodium ion battery in vehicles, and the vehicles include electric vehicles, electric forklifts, electric transport trucks, etc.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] In the sodium supplement additive of the present invention, due to the application of the PVDF graft, compared with the traditional sodium supplement agent, the first coulombic efficiency and energy density of the sodium ion battery can be further improved, the cycle life of the sodium ion battery can be improved, and the difficulty of preparing the battery cell can be reduced.

[0035] PVDF grafts are prepared by reacting hydroxypropyl methacrylate, sodium salt of 2-ethanesulfonate of methacrylate with PVDF. They not only have excellent bonding strength, but also maintain mechanical integrity and high mechanical strength. They can improve the structural uniformity of the positive electrode slurry in the process of preparing sodium ion positive electrode sheets. The application of PVDF grafts can enhance the diffusion of sodium ions at the interface of the electrode and the electrolyte, and can also build a strong protective layer to prevent side reactions and improve the cycle durability under high voltage. This helps to improve the performance of the subsequently assembled batteries and extend the battery life. PVDF grafts are used as adhesives and combined with sodium salts as sodium supplements to the positive electrode sheets. The resulting battery can obtain excellent rate performance at 0.5C, and the capacity retention rate after 400 cycles is as high as more than 98%. In addition, the addition of furfuryl thiopropionate can further optimize the improvement of the electrochemical performance of sodium ion batteries by PVDF grafts.

[0036] Therefore, the present invention provides a sodium supplement additive with high sodium content and stable performance, which can effectively improve the initial coulombic efficiency and energy density of sodium ion batteries, and can also improve the cycle life of sodium ion batteries and reduce the difficulty of battery cell preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 1 is an infrared spectrum of the PVDF grafted product and PVDF according to Example 5 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] Example 1

[0040] Preparation of positive electrode

[0041] S1. Weigh the positive electrode main material Na3V2(PO4)3, conductive agent Super P, adhesive PVDF, and sodium gluconate as a sodium supplement additive; in terms of weight, the total amount of the positive electrode main material, conductive agent, and adhesive is 100%, of which the positive electrode main material accounts for 90%, the adhesive accounts for 5%, and the conductive agent accounts for 5%; the amount of sodium gluconate added is 1.0wt% of the amount of the positive electrode main material.

[0042] S2. Add the weighed positive electrode material, adhesive, and sodium supplement additive into the glue solution in the stirring tank according to the above proportions, control the speed to 20RPM, and stir for 5 hours until the solid is completely dissolved.

[0043] S3. Add the conductive agent into the stirring tank, control the speed to 30RPM and knead for 1h; dilute with NMP to prepare the positive electrode slurry. After adding NMP, the weight proportion of the positive electrode main material, adhesive, sodium supplement additive and conductive agent in the mixture is 70%.

[0044] S4. The positive electrode slurry obtained in S3 was extrusion coated on aluminum foil, with a single-sided coating amount of 0.015 g / cm 2 The positive electrode sheet is obtained through drying, compacting, rolling and cutting.

[0045] Example 2

[0046] Preparation of positive electrode

[0047] S1. Weigh the positive electrode main material Na3V2(PO4)3, the conductive agent Super P and the binder PVDF, and the sodium supplement additive sodium gluconate, wherein the mass ratio of the positive electrode main material Na3V2(PO4)3, the conductive agent Super P and the binder PVDF is 95:3:2; the amount of sodium gluconate used is 0.5wt% of the amount of the positive electrode main material used.

[0048] S2. Add the weighed positive electrode material, adhesive PVDF, and sodium gluconate into the glue solution in the stirring tank according to the above proportions, control the speed to 10RPM, and stir for 6 hours until the solid is completely dissolved.

[0049] S3. Add the conductive agent Super P into the stirring tank, control the speed to 10RPM and knead for 3 hours; add NMP to dilute and prepare the positive electrode slurry. After adding NMP, the weight proportion of the positive electrode main material, adhesive, sodium supplement additive and conductive agent in the mixture is 70%.

[0050] S4. Pour the positive electrode slurry obtained in S3 onto aluminum foil and apply it with a coating applicator. The coating amount on one side is 0.015 g / cm 2 The positive electrode sheet is obtained through drying, compacting, rolling and cutting.

[0051] Example 3

[0052] Preparation of positive electrode

[0053] S1. Weigh the positive electrode main material Na3V2(PO4)3, the conductive agent Super P and the adhesive PTFE, and the sodium supplement additive sodium gluconate, wherein the mass ratio of the positive electrode main material Na3V2(PO4)3, the conductive agent Super P and the adhesive PTFE is 95:3:2; the amount of sodium gluconate used is 0.5wt% of the amount of the positive electrode main material used.

[0054] S2. Add the weighed positive electrode material, adhesive PTFE, and sodium gluconate into the glue solution in the stirring tank according to the above proportions, control the speed to 30RPM, and stir for 4 hours until the solid is completely dissolved.

[0055] S3. Add the conductive agent Super P into the stirring tank, control the speed to 30RPM and knead for 2h; dilute with NMP to prepare the positive electrode slurry. After adding NMP, the weight proportion of the positive electrode main material, adhesive, sodium supplement additive and conductive agent in the mixture is 70%.

[0056] S4. The positive electrode slurry obtained in S3 was extrusion coated on aluminum foil, with a single-sided coating amount of 0.015 g / cm 2 The positive electrode sheet is obtained through drying, compacting, rolling and cutting.

[0057] Example 4

[0058] Preparation of positive electrode

[0059] S1. Weigh the positive electrode main material Na3V2(PO4)3, the conductive agent Super P and the binder PVDF, and the sodium supplement additive sodium gluconate, wherein the mass ratio of the positive electrode main material Na3V2(PO4)3, the conductive agent Super P and the binder PVDF is 98:1:1; the amount of sodium gluconate used is 0.1wt% of the amount of the positive electrode main material used.

[0060] S2. Add the weighed positive electrode material, adhesive PVDF, and sodium gluconate into the glue solution in the stirring tank according to the above proportions, control the speed to 30RPM, and stir for 4 hours until the solid is completely dissolved.

[0061] S3. Add the conductive agent Super P into the stirring tank, control the speed to 30RPM and knead for 2h; dilute with NMP to prepare the positive electrode slurry. After adding NMP, the weight proportion of the positive electrode main material, adhesive, sodium supplement additive and conductive agent in the mixture is 70%.

[0062] S4. Pour the positive electrode slurry obtained in S3 onto aluminum foil and apply it with a coating applicator. The coating amount on one side is 0.015 g / cm 2 The positive electrode sheet is obtained through drying, compacting, rolling and cutting.

[0063] Example 5

[0064] Preparation of PVDF grafted polymers

[0065] Through the ATRP method, under the protection of nitrogen, hydroxypropyl methacrylate and sodium salt of 2-ethanesulfonate methacrylate were grafted onto PVDF with PVDF as the substrate.

[0066] The PVDF grafted product was prepared according to the ratio of 5 mL of hydroxypropyl methacrylate and 0.4 g of sodium methacrylate 2-ethanesulfonate per 10 g of PVDF. DMF was used as solvent and CuCl was used as catalyst during the reaction.

[0067] Specifically, PVDF powder was added into DMF at a ratio of 75 mL DMF per 10 g PVDF, and heated and stirred at 50° C. until the powder was completely dissolved.

[0068] Weigh hydroxypropyl methacrylate monomer and DMF according to the proportion, stir to dissolve, then add methacrylate 2-ethanesulfonate sodium salt, stir to fully mix methacrylate 2-ethanesulfonate sodium salt and hydroxypropyl methacrylate. The dosage ratio of each material is: 75mL DMF for every 5mL hydroxypropyl methacrylate, 0.4g methacrylate 2-ethanesulfonate sodium salt. Add the DMF solution of the dissolved PVDF powder mentioned above.

[0069] Under the protection of nitrogen, ATRP reaction was carried out. CuCl and DMF were added to the above solution in the ratio of 60 mg CuCl and 5 mL DMF per 10 g PVDF. The reaction temperature was controlled at 90 ° C and the reaction time was 6 h under constant temperature stirring. After the reaction was completed, when the mixture was cooled to room temperature, an excess of petroleum ether-ethanol with a volume ratio of 1:1 was added for precipitation, and the precipitate was obtained by centrifugation, and the precipitate was repeatedly washed with a large amount of ethanol-water with a volume ratio of 1:1. Finally, the obtained precipitate was dried to obtain a PVDF grafted product. The drying temperature was 70 ° C and the drying time was 24 h.

[0070] IS50 Fourier transform infrared spectrometer was used to characterize the PVDF grafted product obtained after 6 h of reaction and the raw material PVDF. The samples were prepared by potassium bromide tableting method with a scanning wavelength range of 500 cm -1 ~4000cm -1 ; Scan line number is 32; Resolution is 4cm -1 The infrared spectrum obtained is shown in Figure 1 As can be seen from the figure, PVDF has a -1 and 1187cm -1 There is a pair of characteristic absorption peaks caused by the stretching vibration of CF. As the ATRP reaction proceeds, the peaks at 1730 cm -1 A new C=O stretching vibration peak appears at 1148 cm -1 A new stretching vibration peak of CN appears at 1280 cm -1 The stretching vibration peak of CF at 1187 cm -1 The stretching vibration peak of CF overlaps with the stretching vibration peak of CN. Only one broadened peak can be seen in the infrared spectrum at 2900 cm -1 The stretching vibration of the nearby methyl group and the -1 The stretching vibration peak of the nearby methylene group is obvious at 3300cm -1 ~3500cm -1 The stretching vibration peak of OH appears at 1000 cm -1 ~1300cm -1 and 1250cm -1 ~1400cm -1 PVDF grafted products show strong absorption peaks, which can be inferred that PVDF grafted products contain sulfonic acid groups and at 1060 cm -1 and 1120cm -1 The characteristic absorption peaks nearby can also verify the existence of SO and S=O bonds, which can verify that PVDF grafted products are obtained by the reaction.

[0071] Preparation of positive electrode

[0072] Compared with Example 1, the difference between this example and Example 1 is that the adhesive is the PVDF graft obtained above; the other conditions and steps are the same.

[0073] Example 6

[0074] Compared with Example 5, the difference between this embodiment is that the mass ratio of the positive electrode main material, the conductive agent and the adhesive is 98:1:1; the amount of the sodium supplement additive added is 0.1wt% of the positive electrode main material; and the other conditions and steps are the same.

[0075] Example 7

[0076] Compared with Example 5, the difference between this embodiment is that the mass ratio of the positive electrode main material, the conductive agent and the adhesive is 95:3:2; the amount of the sodium supplement additive added is 0.5wt% of the positive electrode main material; and the other conditions and steps are the same.

[0077] Example 8

[0078] Preparation of positive electrode

[0079] Compared with Example 5, the difference between this embodiment and Example 5 is that: during the process of adding the weighed positive electrode main material, adhesive PVDF graft, and sodium gluconate into the glue liquid in the stirring tank in proportion, furfuryl thiopropionate is added, wherein the mass ratio of furfuryl thiopropionate to PVDF graft is 1:3; other conditions and steps are the same.

[0080] Example 9

[0081] Preparation of positive electrode

[0082] Compared with Example 8, the difference between this example is that the mass ratio of furfuryl thiopropionate to PVDF graft is 1:5; other conditions and steps are the same.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 5 lies only in the preparation of the PVDF grafted product.

[0085] Preparation of PVDF grafted products: 2-ethanesulfonic acid methacrylate sodium salt was replaced by hydroxypropyl methacrylate.

[0086] Comparative Example 2

[0087] The difference between this comparative example and comparative example 1 is only the preparation of the PVDF grafted product.

[0088] Preparation of PVDF grafted products: All hydroxypropyl methacrylate was replaced with sodium 2-ethanesulfonate methacrylate.

[0089] Test example

[0090] Preparation of sodium ion batteries

[0091] A hard carbon negative electrode sheet and a PP diaphragm or a PE diaphragm are used, in combination with the positive electrode sheet obtained in the above embodiments and comparative examples, and assembled into a dry battery cell in a stacking manner, and then packaged with an aluminum-plastic film, injected with an electrolyte, and then waited for formation. The upper limit voltage of the formation is controlled to 4.0V-4.5V. The obtained battery cell is further assembled into a battery. Under high voltage, the sodium supplement additive can decompose to produce active sodium to compensate for the sodium consumed by the negative electrode hard carbon.

[0092] Electrochemical performance test

[0093] Battery tests were performed on the batteries prepared in Examples 1-9 and Comparative Examples 1-2, respectively.

[0094] The first charge and discharge capacity of the battery was tested at a rate of 0.1C and its first coulombic efficiency was calculated. The cycle performance was tested at a rate of 1C for 400 cycles. The battery was charged to 3.8V at a constant current and constant voltage of 0.5C and discharged to 1.5V at 0.5C to obtain the capacity of the battery; the weight of the battery cell was measured with a balance to calculate the energy density of the battery cell. The first coulombic efficiency test results of each embodiment and comparative example are shown in Table 1; the positive electrode energy density test results are shown in Table 2; the capacity retention rate test results after 400 cycles are shown in Table 3.

[0095] Table 1 The first coulombic efficiency test results of each embodiment and comparative example

[0096]

[0097] Referring to the data in Table 1, and referring to the data of Example 2 and Example 3, it can be seen that the use of PVDF or PTFE as a binder has little difference in the effect on the first coulombic efficiency of the sodium ion battery. Referring to the data of Examples 1, 2 and Example 4, it can be seen that when PVDF is used as a binder, when the weight ratio of the sodium supplementing additive sodium gluconate to the binder PVDF falls roughly within the range of 0.1-0.9:1-5, the difference in the amount of the two has little difference in the effect on the first coulombic efficiency of the sodium ion battery.

[0098] Continuing to refer to the data in Table 1, it can be seen from the data comparison of Examples 1, 2 and 4 with Examples 5-9 and Comparative Examples 1-2 that in the process of preparing the positive electrode slurry of the sodium ion battery, the sodium supplement additive is used in combination with the PVDF graft relative to PVDF, which can significantly improve the first coulomb efficiency of the sodium ion battery. In addition, it can be seen from the data of Examples 1, 2 and 4 and Examples 5-7 that the sodium supplement additive is used in combination with the PVDF graft relative to PVDF, and the first coulomb efficiency of the sodium ion battery is increased by an average of 7.33%, which is significant; it shows that the PVDF graft has a significant effect on improving the first coulomb efficiency of the sodium ion battery, which may be because the PVDF graft contains related groups of hydroxypropyl methacrylate and / or methacrylate 2-ethanesulfonic acid ester, which makes it have more excellent bonding strength, and can provide more sodium embedding sites, have a higher capacity, and show higher ionic conductivity. It is also possible that the addition of the PVDF graft can weaken the phase transition of the positive electrode slurry, and can improve the structural uniformity and structural stability of the positive electrode slurry in the process of preparing the sodium ion positive electrode sheet.

[0099] Referring to the data of Example 5 and Examples 8 and 9 in Table 1, the first coulombic efficiency of Example 8 is better than that of Example 9 and Example 5, indicating that the addition of furfuryl thiopropionate can optimize the improvement of the first coulombic efficiency of the PVDF graft, and the amount of furfuryl thiopropionate may be positively correlated with the first coulombic efficiency of the sodium ion battery within a certain range. This may be because the presence of heterocyclic rings and carboxylic acid ester groups in furfuryl thiopropionate changes the spatial structure of the PVDF graft during its contact with the PVDF graft, or it may be because furfuryl thiopropionate reacts with the PVDF graft to promote the diffusion of sodium ions in the electrolyte, making up for the slow diffusion of sodium ions due to their larger radius than lithium ions.

[0100] Table 2 Test results of positive electrode energy density of various embodiments and comparative examples

[0101]

[0102] Referring to the data in Table 2, it can be seen from the data of Examples 1, 2 and 4 and Examples 5-7 that, relative to PVDF, the sodium supplement additive and the PVDF graft can significantly improve the positive electrode energy density of the sodium ion battery when used in combination, indicating that the role of the PVDF graft is not only to make up for the positive electrode active sodium ions consumed in the first week of film formation, but also to facilitate sodium ion transport, thereby improving the cycle stability of the battery. This may be because the PVDF graft contains related groups of hydroxypropyl methacrylate and / or methacrylate 2-ethanesulfonate, which makes the structure of the positive electrode sheet more stable and can maintain mechanical integrity, and can improve the structural uniformity of the positive electrode slurry in the process of preparing the sodium ion positive electrode sheet.

[0103] Referring to the data of Example 5 and Examples 8 and 9 in Table 2, the positive electrode energy density of Example 8 is better than that of Example 9 and is better than that of Example 5, indicating that the addition of furfuryl thiopropionate can optimize the improvement effect of PVDF grafts on the positive electrode energy density, and the amount of furfuryl thiopropionate may be positively correlated with the cycle stability of sodium ion batteries within a certain range. This may be because the presence of heterocyclic rings and carboxylic acid ester groups in furfuryl thiopropionate leads to changes in the spatial structure of PVDF grafts, which is conducive to the insertion and extraction of sodium ions; and furfuryl thiopropionate also provides an embedding site for sodium ions, thereby improving electronic and ionic conductivity.

[0104] Table 3 Capacity retention test results after 400 cycles of various embodiments and comparative examples

[0105]

[0106] Referring to the data in Table 3, it can be seen from the data of Examples 1, 2 and 4 and Examples 5-7 that, relative to PVDF, the sodium supplement additive used in combination with the PVDF graft can significantly improve the capacity retention rate of the sodium ion battery. This may be because the sodium supplement additive used in combination with the PVDF graft can enhance the diffusion of sodium ions at the interface between the electrode and the electrolyte, and can also construct a strong protective layer. The addition of related groups of hydroxypropyl methacrylate and / or 2-ethanesulfonic methacrylate weakens the effect of structural changes or phase transitions on electrochemical properties, inhibits phase transitions during sodium deintercalation, improves the cycle stability of the material, prevents side reactions, and improves cycle durability.

[0107] Referring to the data of Example 5 and Examples 8 and 9 in Table 3, the capacity retention rates of Examples 8 and 9 after 400 cycles are better than those of Example 5, indicating that the addition of furfuryl thiopropionate can optimize the improvement effect of PVDF grafts on the capacity retention rate of sodium ion batteries.

[0108] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.

[0109] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

Claims

1. A sodium ion battery positive electrode sheet, comprising: A base layer, and a functional layer attached to the base layer, wherein the functional layer has an adhesive, the adhesive includes a PVDF graft, and the PVDF graft has a hydroxypropyl methacrylate group and a methacrylate 2-ethanesulfonate group; the functional layer also contains at least one of a positive electrode main material, a conductive agent and a sodium supplement additive, and the sodium supplement additive includes at least one of sodium carbonate, sodium oxalate, sodium gluconate, and sodium acetate; by weight, the amount of the positive electrode main material is 90-98 parts, the amount of the adhesive is 1-5 parts, and the amount of the conductive agent is 1-5 parts; the amount of the sodium supplement additive is 0.1-1.0wt% of the amount of the positive electrode main material; The PVDF graft is prepared by reacting hydroxypropyl methacrylate, sodium methacrylate 2-ethanesulfonate and PVDF; in the preparation of the PVDF graft, 4mL-6mL hydroxypropyl methacrylate and 0.2g-0.5g sodium methacrylate 2-ethanesulfonate are used for every 10g PVDF; When PVDF grafted material is used as an adhesive, furfuryl thiopropionate is also added, wherein the mass ratio of furfuryl thiopropionate to PVDF grafted material is 1:3-5.

2. The sodium ion battery positive electrode sheet according to claim 1, characterized in that: The base layer includes a metal-based material or an alloy-based material, and the metal-based material includes an aluminum-based material or a copper-based material.

3. The sodium ion battery positive electrode sheet according to claim 2, characterized in that: The aluminum-based material includes aluminum foil; or, the positive electrode main material includes at least one of layered oxides, Prussian blue and its analogs, and polyanionic compounds; or, the conductive agent includes at least one of carbon materials, metal oxides, and conductive polymers.

4. A method for preparing a positive electrode sheet for a sodium ion battery, comprising: The positive electrode main material, the adhesive and the sodium supplement additive are mixed, and then a conductive agent is added to prepare a positive electrode slurry; the adhesive includes a PVDF graft, and the PVDF graft has a hydroxypropyl methacrylate group and a methacrylate 2-ethanesulfonate group; Applying the positive electrode slurry onto the substrate layer to prepare a positive electrode sheet for a sodium ion battery; The PVDF graft is prepared by reacting hydroxypropyl methacrylate, sodium methacrylate 2-ethanesulfonate and PVDF; in the preparation of the PVDF graft, 4mL-6mL hydroxypropyl methacrylate and 0.2g-0.5g sodium methacrylate 2-ethanesulfonate are used for every 10g PVDF; When PVDF grafted material is used as an adhesive, furfuryl thiopropionate is also added, wherein the mass ratio of furfuryl thiopropionate to PVDF grafted material is 1:3-5.

5. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 4, characterized in that: By weight, the amount of the positive electrode main material is 90-98 parts, the amount of the adhesive is 1-5 parts, and the amount of the conductive agent is 1-5 parts; the amount of the sodium supplement additive is 0.1-1.0wt% of the amount of the positive electrode main material.

6. A sodium ion battery, comprising the sodium ion battery positive electrode sheet according to claim 1.

7. A vehicle comprising the sodium ion battery according to claim 6.

Citation Information

Patent Citations

  • Positive electrode material and preparation method therefor, positive electrode plate, and sodium ion battery

    WO2023097984A1

  • Sodium-free negative electrode sodium battery with high energy density

    CN116683017A

  • Binder for Secondary Battery And Secondary Battery Comprising The Same

    KR1020160066498A